Mutações do leitor, da mídia e da aprendizagem: proposta de aplicativo para alfabetização hipermidiática lúdica e interativa - Botelho, Thaïs Helena Falcão (2019)
The issue of this dissertation arises from the changes that occurred from the digitization of languages, which allowed the creation and visualization contents in which signs of a verbal, visual and auditory nature are mixed and coexist. Faced with such transformations, there is a need to propose new learning processes in education, in which other languages other than written can be included pedagogically and systematically. With this need in mind, this study was developed through two types of paths: the first, academic and more extensive; the second, the didactic creation proposal. The first path used some changes, throughout history, that converged and collaborated in the processes of creation, and production of different languages, focusing primarily on written language and its learning. Two theoretical basis were used to follow this path. The first theory, by Magda Soares, understand that the process of learning the written language would have three facets: linguistics, interactive and sociocultural. The second theoretical basis, by Lucia Santaella, presents the development over the centuries of five types of readers: contemplative, moving, immersive, ubiquitous and the prosumer reader. Together, the two theories helped to understand the integrated evolution of the reader, the media, and learning with a greater focus on written language. This evolution, seen in an integrated way, allows a better understanding of the current gap in the learning of other types of languages in educational contents. In the second path, a proposal is presented for a first pilot script for a digital object to be realized in hypermedia. It would be a component of the One Touch to the World hypermedia application for literacy. The intention is, to demonstrate in a simple and objective way - for readers, educators and producers - that this new proposal of hypermedia literacy, fits congruently, and feasibly in to the basic pedagogical processes and necessities for the students and teachers of the 21st century